THE EFFECT OF ENGLISH AND CANTONESE SPEAKING ABILITY OF THE INDONESIAN FEMALE MIGRANT WORKERS IN HONGKONG TOWARD PEOPLE AROUND THEM - budi rachmawati (Journal of English Language and Literature (JELL), 2018)
The globalization era, requires some life aspects to be mastered. One of the aspects is the ability to communicate among others in any languages as communication tool to interact with the world community. The fact that Indonesia migration of labors had a big number of portion since the Dutch East Indies Government, makes the mastery of foreign language important. Most of the migrant workers of Indonesia are women. They migrate abroad because of economic difficulties. For that, they are willing to become domestic helper to improve the economic conditions of their families. Having enough and compatibel skills are very important to minimize the problems that arise with the fellow and people around them. The training for these migrant workers are conducted by Indonesian Manpower Supplier (PJTKI) where they can get such Training Center-Foreign Affairs (BLK –LN). By doing the training, the migrant workers will get some skills like basic skill and interpersonal skills. Female migrant workers get English and cantonese language, especially for those who work in Hongkong. The training is done in 4 months including daily foreign language speaking practice. The objective of the training are to help the female migrant workers in bargaining position and more appreciate existence